Coffee Infusions: Can They Be a Source of Microelements with Antioxidant Properties? - Ewa Olechno (MDPI AG, 2021)
Coffee is a beverage that is very popular all over the world. Its pro-health effect has been demonstrated in many publications. This drink can counteract the effects of oxidative stress thanks to its antioxidant properties. The aim of this study was to collect data on the content of microelements with antioxidant activity (manganese, zinc, copper, iron) in coffee infusions, taking into account various factors. The study considered publications from the years 2000–2020 found in Google Scholar and PubMed databases. It was noted that coffee can provide up to 13.7% of manganese requirements per serving, up to 4.0% and 3.1% of zinc requirements for women and men, up to 2.7% and 2.1% of copper requirements for women and men, and up to 0.4% and 0.6% of iron requirements for women and men. Coffee infusions can also be a source of fluoride (up to 2.5%), chromium (up to 0.4% of daily intake for women and 0.2% for men), and cobalt (up to 0.1%). There are no data in the literature regarding the content of selenium in coffee infusions. The origin of coffee beans and the type of water used (especially regarding fluoride) may have an impact on the content of minerals in infusions. The brewing method does not seem to play an important role. As it is a very popular beverage, coffee can additionally enrich the diet with such micronutrients as manganese, zinc, and copper. This seems beneficial due to their antioxidant properties, however the bioavailability of these elements of coffee should be taken into account. It seems necessary to carry out more research in this area.